Heart rate, ejection duration and subendocardial viability ratio in patients with rheumatoid arthritis as compared to controls. (24th January 2013) - Pieringer, Herwig; Brummaier, Tobias; Schmid, Michael; Pichler, Max; Hayat‐Khayyati, Avida; Ebner, Stefan; Biesenbach, Georg; Pohanka, Erich
Abstract Aim Rheumatoid arthritis (RA) is associated with increased cardiovascular morbidity and mortality. In the general population, an increased heart rate is associated with increased mortality. Only a few studies have investigated heart rate in RA patients and compared the results with patients that do not have RA (n‐RA). Therefore, little is known as to whether an increased heart rate, at least in part, could explain the increased mortality found in RA patients. The aim of the present study was to investigate whether heart rate is increased in RA patients. Methods In this cross‐sectional study, heart rate was determined in a total of 282 patients (131 RA, 151 n‐RA). In addition, non‐invasive pulse wave analysis of the radial artery was performed to determine cardiac ejection duration using the Sphygmocor apparatus. Furthermore, the subendocardial viability ratio (SEVR), a marker of cardiac workload, was investigated, whereby higher values indicate a more favorable supply/demand relationship for the myocardium. Patients using chronotropic drugs were not included in the study. Results Heart rate was virtually the same in RA patients (71.9 ± 11.2 beats/min [bpm]) as compared with controls (72.3 ± 11.7 bpm; P > 0.05). Also SEVR (RA 144 ± 25% vs. n‐RA 147 ± 27%; P > 0.05) and ejection duration (RA 321 ± 24 ms vs. n‐RA 318 ± 24 ms; P > 0.05) were comparable between the groups. Conclusion It could not be shown that heart rate in RA patients differs significantly from heart rate in controls. Therefore, heart rate does not appear to explain or contribute to the increased cardiovascular risk found in RA patients.